Molecular packing and the handedness of the self-assemblies of C17H35CO-Ala-Phe sodium salts. (2nd October 2017) - Lin, Shuwei; Li, Yi; Li, Baozong; Yang, Yonggang
Abstract : Molecular packing structure dominates the handedness of the self-assemblies of a series of lipodipeptide sodium salts. Abstract : The handedness of the self-assemblies of several series of homogeneous lipodipeptide sodium salts is controlled by the chirality of the amino acid at the C-terminus. This phenomenon is named the "C-terminal determination" rule. Herein, four heterogeneous C17 H35 CO-Ala-Phe sodium salts, designed and synthesized by changing the chirality of the amino acids, were able to self-assemble into twisted nanoribbons in deionized water. The handedness of the nanoribbons was controlled by the chirality of the alanine, which does not follow the "C-terminal determination" rule. This phenomenon might be because the homochiral and heterochiral lipodipeptide sodium salt molecules packed into different structures. The X-ray diffraction and circular dichroism characterizations indicated that the molecules self-assembled into an interdigitated bilayer structure and there were no strong π–π stackings between neighboring phenyl groups.